2012
DOI: 10.1371/journal.pone.0031756
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Cleavage Specificity of Human Thrombin

Abstract: Thrombin is one of the most extensively studied of all proteases. Its central role in the coagulation cascade as well as several other areas has been thoroughly documented. Despite this, its consensus cleavage site has never been determined in detail. Here we have determined its extended substrate recognition profile using phage-display technology. The consensus recognition sequence was identified as, P2-Pro, P1-Arg, P1′-Ser/Ala/Gly/Thr, P2′-not acidic and P3′-Arg. Our analysis also identifies an important rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
126
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(142 citation statements)
references
References 58 publications
10
126
1
Order By: Relevance
“…Such methods include engineering deletion mutants (3), use of competitive ligands (4,5), and site-directed mutagenesis (6,7). In contrast to these techniques, substrate phage display is a highthroughput, unbiased approach to studying protease substrate specificity (8)(9)(10). In this method, a library consisting of 10 6 -10 9 independent phage clones, each expressing a unique potential substrate on its surface, is panned for multiple rounds with a protease, and the cleaved or uncleaved phages after each reaction are removed and amplified for subsequent rounds of selection.…”
mentioning
confidence: 99%
“…Such methods include engineering deletion mutants (3), use of competitive ligands (4,5), and site-directed mutagenesis (6,7). In contrast to these techniques, substrate phage display is a highthroughput, unbiased approach to studying protease substrate specificity (8)(9)(10). In this method, a library consisting of 10 6 -10 9 independent phage clones, each expressing a unique potential substrate on its surface, is panned for multiple rounds with a protease, and the cleaved or uncleaved phages after each reaction are removed and amplified for subsequent rounds of selection.…”
mentioning
confidence: 99%
“…Angewandte Communications 326 www.angewandte.org uncleaved probe, in which FRET was intact (Figure 2, blue), from cleaved probe, in which FRET was disrupted (Figure 2, red). Images confirmed that RACPP PPRSFL (10) and RACPP DPRSFL (5) are cleaved by thrombin in a time-dependent manner and that RACPP PPRSFL (10) is selective for thrombin. An MMP cleavable RACPP PLGC(Me)AG (20) was also shown, as a control that was not cleaved by any of the procoagulation enzymes.…”
mentioning
confidence: 75%
“…Mice were fed a 0.5 % cholesterol diet (Harlan Laboratories) for 3-6 months. [30] Intraoperative imaging of atherosclerotic plaques was performed 2.5 h after intravenous injection of 10 nmol of RACPP DPRSFL (5). Prior to imaging, animals were anesthetized with ketamine/xylazine (100 mg kg À1 , 10 mgkg À1 ) and the carotid arteries were exposed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations